Dinamika Pemilihan Gubernur Jawa Timur - R. Nazriyah (Jurnal Hukum IUS QUIA IUSTUM, 2013)
This research is aimed at finding the reasons of the Board of Trustees of the General Election Committee (DKPP) in granting the charge of Khofifah Indar Parawansa and the reasons of the Constitutional Court in rejecting the charge related with the Regional Head Election of East Java in 2013. This research is a normative research with the approaches used consisting of Acts and Case studies. The data used are secondary data involving primary legal material, secondary legal material, and tertiary legal material. The data collected were then analyzed qualitatively. The result of the research concludes that according to the Costitutional Court, the Jalan Lain Menuju Kesejahteraan Rakyat (Jalin Kesra) program conducted by Soekarwo is not a fatal mistake in the Regional Head Election. According to the Constitutional Court, the program is a sustainable program initiated and conducted since 2010. Meanwhile, the consideration of DKPP to grant the charge of Khofifah-Herman is because the General Election Committee was proven of diminishing the party constitutional right to suggest a candidate in the Regional Head Election of East Java including Khofifah-Herman for the candidate for governor and deputy governor. The grant and social assisstance (bansos) program must be conducted in the first three years of the regional head governance so that there will not be an allegation of the grant and social assistance manipulation for campaign activities if the incumbent plans to be reelected.